A Reassessment of the Taxonomic Position of Mesosaurs, and a Surprising Phylogeny of Early Amniotes - Laurin, Michel; Piñeiro, Graciela H. (Frontiers in Earth Science, 2017)
We reassess the phylogenetic position of mesosaurs by using a data matrix that is updated and slightly expanded from a matrix that the first author published in 1995 with his former thesis advisor. The revised matrix, which incorporates anatomical information published in the last twenty years and observations on several mesosaur specimens (mostly from Uruguay) includes seventeen terminal taxa and 129 characters (four more taxa and five more characters than the original matrix from 1995). The new matrix also differs by incorporating more ordered characters (all morphoclines were ordered). Parsimony analyses in PAUP 4 using the branch and bound algorithm show that the new matrix supports a position of mesosaurs at the very base of Sauropsida, as suggested by the first author in 1995. The exclusion of mesosaurs from a less inclusive clade of sauropsids is supported by a Bremer (Decay) index of 4 and a bootstrap frequency of 66%, both of which suggest that this result is moderately robust. The most parsimonious trees include some unexpected results, such as placing the anapsid reptile Paleothyris near the base of diapsids, and all of parareptiles as the sister-group of younginiforms (the most crownward diapsids included in the analyses). Turtles are placed among parareptiles, as the sister-group of pareiasaurs (and in diapsids, given that parareptiles are nested within diapsids). This unexpected result offers a potential solution to the long-lasting controversy about the position of turtles because previous studies viewed a position among diapsids and among parareptiles as mutually exclusive alternatives.